Pengaruh bauran promosi dan gaya hidup terhadap minat beli pada kedai kopi serasi - Yosie Anne Putri (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2019)
The purpose of this research is to understand the influence of promotion mix and lifestyle towards purchase intention of Kedai Kopi Serasi product. This research is a quantitative research with 130 respondent of sample which are consumers of Kedai Kopi Serasi in Cilincing who coincidentally met with the researcher if deemed concerned was appropriate to be used as a source of data by using non-probability sampling method and incedential sampling techniques. The result of this research show that promotion mix influence significantly to purchase intention and lifestyle influence significantly to purchase intention. The implications of this research can be a reference for the management team in formulating Kedai Kopi Serasi increase purchase intention strategy through promotion mix and lifestyle.